Շարքային կազմի պայմանագրային զինծառայողների վաղաժամկետ զորացրման որոշ հոգեբանական առումները և կանխարգելման ուղիները - Յարամիշյան, Վ.
Досрочное увольнение в запас военнослужащих рядового состава, несущих службу по контракту, является сложно решаемой проблемой для любой современной армии. Суть проблемы в том, что для подготовки военнослужащих по контракту государством и армией расходуются немалые средства, а преждевременное увольнение военнослужащих-контрактников по их инициативе сводит на нет эти усилия. В данной статье сделана попытка системного анализа психологических аспектов тех причин, которые служат основой для преждевременного отказа от службы. Автором разработаны и предложены некоторые пути разрешения данной проблемы. Обсуждаемые проблемы относятся к одной из трех групп перечисленных причин. Это проблемы, связанные с личностью военнослужащего, с условиями несения службы и со сферой межличностных отношений. Подчеркивается важность мобилизации усилий и согласования целенаправленных действий, предпринимаемых всеми структурами, в том числе, командирами, штабами, офицерами-психологами по улучшению условий несения службы. The early transfer to the reserve of the military personnel of ordinary structure, serving under the contract, is difficult solved problem for any modern army. The problem essence is that for preparation of contract servicemen by the state and army considerable funds are spent, and the premature dismissal of the military personnel-contract employees, on their initiative nullifies these efforts. In this article it is made attempt of the system analysis of psychological aspects of those reasons, which form a basis for premature refusal of service. The author developed and offered some ways of permission of this problem. Discussed problems belong to one of three groups of the listed reasons. These are the problems connected with the identity of the serviceman, with conditions of service and with the sphere of the interpersonal relations. Importance of mobilization of efforts and coordination of the purposeful actions undertaken by all structures, including commanders, staffs and officers-psychologists on improvement of conditions of service is emphasized.
Keywords: Հոգեբանություն